Pengaruh Kualitas Produk dan Kualitas Layanan terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen - Elisa Nanda Lutvi (Fakultas Ekonomi dan Bisnis, 2023)
This research aims to examine the influence of product quality and service quality on customer loyalty through customer satisfaction at KFC in Jember. This study is an explanatory research that aims to demonstrate the position and influence between the variables under investigation. The sample in this study consisted of 100 respondents selected through purposive sampling. This research uses quantitative data. The data source in this research is primary data by distributing questionnaires directly to selected respondents. The research instrument used path analysis with the Statistical Program For Social Science (SPSS). The results show: Product quality has a significant effect on consumer satisfaction. Service quality has a substantial effect on consumer satisfaction. Product quality has a significant effect on customer loyalty. Consumer satisfaction has a significant effect on customer loyalty. Product quality has a significant effect on customer loyalty through consumer satisfaction. Service quality has a significant effect on customer loyalty through consumer satisfaction. The findings of this research are that service quality does not have a significant effect on customer loyalty.
Reuploud Repository hasyim Mei 2026 Approved by Teddy
Keywords: Product Quality; Service Quality; Customer Loyalty; Customer Satisfaction.